PERLINDUNGAN HUKUM TERHADAP HAK CIPTA LAGU “LAGI SYANTIK” ATAS PERUBAHAN LIRIK LAGU TANPA SEIZIN PENCIPTA - Cindy Chandra; Gunardi Lie; Moody Rizqy Syailendra P. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The development of an advanced industry has made the entertainment world experience modernization and digitization as evidenced by the availability of various places to channel creativity, especially in the art of music in the form of songs. The musical art work also has intellectual property rights (IPR) which must be protected as a form of legal protection for the creator so that the copyrighted work can continue to work, innovate, and get appreciation from the public. IPR has two types, namely copyright and industrial property rights. Industrial property rights are rights that protect a company from various kinds of plagiarism and can also regulate everything in an industrial environment. UU no. 28 of 2014, copyright is the exclusive right of the creator that arises automatically based on declarative principles after a work is realized in a tangible form without reducing restrictions in accordance with the provisions of laws and regulations. Even so, there are still many cases of copyright infringement such as changing song lyrics, plagiarism, changing song lyrics, and producing videos without permission from the creator. As in the case that ensnared the family of Gen Halilintar who had violated the copyright of the song lagisyantik belonging to singer Siti Badriah in 2018. In this case, PT Nagaswara as the record label demanded Gen Halilintar compensation of 9.5 billion rupiah for the song covered on Gen Halilintar'syoutube account. This research was conducted with the aim of knowing the form of copyright infringement regarding the re-sung syantik song and how to resolve the violation of the copyright.